Hubungan Status Gizi dan Siklus Menstruasi dengan Kejadian Anemia pada Remaja Putri - Fita, Ayu; Fatmawati, Tina Yuli; Putri, Satiti Kawuri (Jurnal Akademika Baiturrahim Jambi, 2025)
Anaemia is a condition in which the body does not have enough iron reserves to distribute to the body's tissues. Adolescent girls suffer from anaemia when the haemoglobin (Hb) level in the blood is less than 12 g/dl. The purpose of this study was to determine the relationship between nutritional status and menstrual cycle with the incidence of anaemia in adolescent girls of Aliyah PKP Al-Hidayah Jambi Province. This type of research is quantitative research with cross-sectional design. The  sample of 77 adolescent Aliyah   girls. The sampling technique used was proportional random sampling technique. The data collection techniques were by filling out questionnaires, measuring body weight, height and Hb. Data analysis in the study used univariate and bivariate analysis using Spearman correlation test. The results of this study showed that the percentage of abnormal nutritional status was 40 people (51.9%), abnormal menstrual cycle was 47 people (61%) and the incidence of anaemia was 38 people (49.4%). There is a significant relationship between nutritional status and incidence of anaemia (p=0.000) and there is a significant relationship between menstrual cycle and incidence of anaemia (p=0.000). It is recommended for adolescent girls to maintain their nutritional status by implementing a healthy diet and a good lifestyle so as to reduce the incidence of anemia in adolescent girls